Fructophilic yeasts to cure stuck fermentations in alcoholic beverages - Sutterlin, Klaus A. (Klaus Alfred) (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhDAgric (Viticulture and Oenology. Wine Biotechnology))--University of Stellenbosch, 2010.